The United States and the rule of law in international affairs - Murphy, John Francis (Cambridge University, 2013)
John Murphy offers an insightful analysis of why the United States does not always accept the rule of law in international affairs. He explains how the nature of the US legal system and the idiosyncrasies of the international legal process combine to compound problems for the US and he explores several alternatives.